Financial Independence Ratio Analysis Of The Regional Government Apbd Of Seluma Regency - Martika, Rengga; Susanti, Neri; Harwini, Dewi (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to determine the Financial Independence Ratio, Efficiency Ratio, and Effectiveness Ratio of the Seluma Regency Regional Government's Regional Budget (APBD). The method used in this study is quantitative, by looking at the financial independence ratio, efficiency ratio, and effectiveness ratio of the Seluma Regency Government's Regional Budget (APBD) for the 2020-2024 period. The results show that the financial independence ratio related to Local Own-Source Revenue (PAD) for the years 2020–2024 has an average value of 71.99%, which is considered less effective. Meanwhile, transfers from the central government show an average value of 97.99%, which is considered effective. The results of the efficiency ratio calculation for the average total regional expenditure of the Seluma Regency Government from 2020 to 2024 amount to 93.40%, which is considered less efficient. Likewise, the average regional revenue of the Seluma Regency Government during the same period is 96.61%, also categorized as less efficient. Furthermore, the effectiveness ratio, based on the average calculation of the achievement of PAD goals and objectives from 2020 to 2024, is 62.45%, which is considered less effective. In contrast, the calculation of total regional expenditure shows an average of 96.61%, which is categorized as effective.